Nebivolol, But Not Metoprolol, Treatment Improves Endothelial Fibrinolytic Capacity in Adults With Elevated Blood Pressure - Stauffer, Brian L. (J Am Heart Assoc, 2017)
BACKGROUND: Vascular endothelial fibrinolytic function is impaired in adults with prehypertension and hypertension and plays a mechanistic role in the development of atherothrombotic events. The influence of β‐blockers on endothelial fibrinolysis is unknown. This study compared the effects of chronic nebivolol and metoprolol treatment on endothelial tissue‐type plasminogen activator (t‐PA) release in adults with elevated blood pressure (BP). METHODS AND RESULTS: Forty‐four middle‐aged adults (36% women) with elevated BP completed a 3‐month, double‐blind, randomized, placebo‐controlled trial comparing nebivolol (5 mg/d), metoprolol succinate (100 mg/d), and placebo. Net endothelial t‐PA release was determined in vivo in response to intrabrachial infusions of bradykinin and sodium nitroprusside before and after each intervention. In a subset, the dose‐response curves to bradykinin and sodium nitroprusside were repeated with a coinfusion of the antioxidant vitamin C. At baseline, resting BP and endothelial t‐PA release were comparable between the 3 groups. BP decreased to a similar extent (≈10 mm Hg) in the nebivolol‐ and metoprolol‐treated groups. There was a substantial increase (≈30%; P<0.05) in the capacity of the endothelium to release t‐PA following chronic treatment with nebivolol but not metoprolol or placebo. Mitigating oxidant stress with vitamin C coinfusion potentiated t‐PA release (90%; P<0.05) at baseline in all groups. However, after the intervention, t‐PA release was unchanged by vitamin C coinfusion in the nebivolol group only. CONCLUSIONS: Nebivolol but not metoprolol improves endothelial t‐PA release in adults with elevated BP. This may be an important vascular benefit of nebivolol. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01595516.